Artificially engineered metaconcrete with wide bandgap for seismic surface wave manipulation. (1st February 2023) - Chen, Zhenyu; Wang, Guifeng; Lim, C.W.
Graphical abstract: Highlights: Novel engineered metaconcrete approach is established for surface Rayleigh wave attenuation. Highly efficient wave attenuation zone is realized with wide bandwidths. Mechanism of acoustic rainbow trapping and mode conversion is presented. Actual earthquake records are applied to validate the performance of metabarriers. Abstract: The energy of ground-born vibration is transported mostly by surface waves. Therefore, engineered structures which absorb externally applied energy and improve structural performance against explosive dynamic loading are highly desired. In this paper, we demonstrate the application of designed metamaterial barriers with engineered metaconcrete for reflecting and redirecting surface Rayleigh waves to avoid disastrous consequences. The metabarrier is constructed by embedding metaconcrete cubes in a semi-infinite space. The local resonance type metaconcrete cell is composed of a heavy lead ball coated by a soft rubber layer and mortar. One significant limitation of metaconcrete is the narrow bandwidth. Here, we apply an array of metaconcretes where the radii of the lead ball and soft coating increase or decrease simultaneously. Via transmission ratio analysis, we show that the metaconcrete-based metabarrier is able to achieve broadband wave attenuation. More interestingly, the elastic wave trapping and surface wave mode conversion can be realized and controlled by the metabarrier. The mechanism of trapping and conversion is fully explained with an unconventional dispersion relation. A time history analysis based on several actual earthquake records obtained from public database is also presented. The result in this paper highlights new applications of metaconcretes and it can be applied to novel seismic shields for protecting civil infrastructures against seismic destruction.